A computational approach to optical and charge carrier properties of organic semiconductors - Turan, Haydar Taylan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2017., 2016)
In this study, the structural and optical properties of various organic semiconductors have been computationally investigated. In the first part, linear and nonlinear optical properties of a series of bis(E-dimesitylborylethenyl)-substituted arenes have been modeled by high-level computational protocols. The former compounds show a remarkable interest as infrared two-photon absorbers and hence may be used in the field of optical active and smart materials or for energy storage purposes. Excited state topologies, absorption and emission spectra, excited state metrics, natural transition orbitals and two-photon absorption cross-section of a series of chromophores have been computed by means of density functional theory (DFT) and time dependent DFT (TD-DFT). Extended benchmark tests on the performance of different functionals have been used. Dynamic and vibronic effects on absorption and emission spectra have been taken into account by sampling the conformational space by means of the Wigner distribution. Important infrared two photon absorption cross sections involving transitions to the second excited state have been observed. In the second part, aim of the study was to understand the unusual electron mobility loss of a bifuran derivative. A benchmark test was performed to choose the ideal functional/basis set combination. Potential energy scans, reorganization energies and transfer integrals of two bifuran and bithiophene derivatives have been performed to analyze intramolecular and intermolecular charge transfers in the molecules. The study shows that lack of intermolecular charge transportation was the reason behind the electron mobility loss in the bifuran derivative compared to the bithiophene derivative.
Keywords: Organic semiconductors.